Digital Preservation of Kampong Bharu: A Mobile Navigator to Assist Exploration of Kampong Bharu - Din, Suhaili; Mohd Razif, Muhammad Haikal (Journal of Computing Technologies and Creative Content, 2021)
One of the historical places in Kuala Lumpur, Malaysia, is Kampong Bharu. Kampong Bharu is well known for its traditional houses and cuisine. Started as a Malay agricultural reservation now transformed into a township where you can enjoy a day of strolling around wooden stilt homes; coconut and banana trees; against the backdrop of the city’s modern skyscrapers. To enjoy the culture and delicacies that cannot be found anywhere else in the district, many tourists, both local and foreign, visit Kampong Bharu. Currently, Kampong Bharu is only known for food but not many knows on the cultural and heritage that it still preserves. The aim of this project is to develop a mobile navigator to aid visitors exploring Kampong Bharu while promoting and preserving information on food, cultural and heritage values of Kampong Bharu digitally. The Mobile Application was developed using Xamarin Forms and the evaluation of its effectiveness was assessed through the results obtained using online questionnaires.